Overcoming gender gaps in rural mechanization: Lessons from reaper-harvester service provision in Bangladesh - Theis, Sophie; Sultana, Nasrin; Krupnik, Timothy J.; International Maize and Wheat Improvement Center; International Rice Research Institute (International Food Policy Research Institute, 2018)
Custom hiring of labor- and cost-saving agricultural machinery services is increasingly common in South Asia. We studied the gendered differences in women’s and men’s involvement in emerging markets for reaper-harvester machinery services in the Feed the Future Zone in Bangladesh. We find that women benefit from managing and sometimes owning machinery services, as well as from the direct and indirect consequences of hiring such services to harvest their crops. However, a number of technical, economic, and cultural barriers constrain women’s full participation in these benefits. The brief provides suggestions for initiatives promoting rural machinery services to more fully engage women, as business owners and users of machinery, to expand the benefits of these markets, with relevance for South Asia and other farming geographies dominated by smallholders.